Patient-reported swelling in arthralgia patients at risk for rheumatoid arthritis: is it of value? - Boeren, Anna M P (Rheumatology (Oxford), 2023)
OBJECTIVE: Patients with clinically suspect arthralgia (CSA) are at risk for developing rheumatoid arthritis (RA). These patients often report joint swelling while this is not objectified by physical examination. To explore the value of patient-reported swelling in CSA, we aimed to determine its association with subclinical joint inflammation on imaging and RA development. METHODS: In two independent, similarly designed CSA cohorts from the Netherlands, symptomatic patients at risk for RA were studied. At baseline, patients indicated whether they had experienced swelling in hand joints. Subclinical joint inflammation was assessed with MRI or US. Patients were followed for inflammatory arthritis development. RESULTS: In total, 534 CSA patients from two independent cohorts were studied, and patient-reported swelling was present in 57% in cohort 1 and in 43% in cohort 2. In both cohorts patient-reported swelling was associated with subclinical joint inflammation. Using MRI, it associated specifically with tenosynovitis (odds ratio [OR] 3.7 [95% CI: 2.0, 6.9]) and when using US with synovitis (OR 2.3 [95% CI: 1.04, 5.3]). CSA patients with self-reported swelling at baseline developed arthritis more often, with hazard ratios of 3.7 (95% CI: 2.0, 6.9) and 3.4 (95% CI: 1.4, 8.4) in cohort 1 and 2, respectively. This was independent of clinical predictors (e.g. morning stiffness), autoantibody positivity and US-detected subclinical joint inflammation. However, when corrected for MRI-detected subclinical joint inflammation, self-reported swelling was no longer an independent predictor. CONCLUSION: Patient-reported joint swelling in CSA relates to subclinical joint inflammation and is an independent risk factor for RA development, but it is less predictive than the presence of MRI-detected subclinical joint inflammation.